SETTLEMENT OF MEDICAL DISPUTES THROUGH THE FORUM OF THE INDONESIAN MEDICAL DISCIPLINE HONORY ASSEMBLY (MKDKI) BASED ON THE PROVISIONS OF ARTICLE 66 OF LAW NUMBER 29 OF 2004 CONCERNING MEDICAL PRACTICE - Dwi Atmoko (Awang Long Law Review, 2022)
Doctors are one of the professions that get the public spotlight, because the nature of their service to the community is very complex. Lately, many people have been highlighting the performance of doctors, both the spotlight delivered directly to the Indonesian Doctors Association (IDI) as the parent organization of doctors, and broadcast through print and electronic media. Disputes between doctors and patients often arise because of the inharmonious relationship between doctors or hospitals and patients. Health disputes that begin with a gap in perceptions and interests between patients and health service providers (doctors and/or hospitals) often lead to legal settlements. There are several ways that patients can choose to solve their problems, one of which refers to Article 66 of Law Number 29 of 2004 concerning Medical Practice. In this study, the author uses a normative legal research method. In addition to using the normative legal method, the author also uses a legal approach and a concept approach in order to provide answers to the problems studied. The results showed that the Indonesian Medical Discipline Honorary Council (MKDKI) was the institution authorized to determine whether there were errors made by doctors and dentists in the application of medical and dental disciplines, and to impose sanctions. The procedure for complaints as referred to in Article 66 of Law Number 29 of 2009 concerning Medical Practice is carried out by MKDKI based on Indonesian Medical Council Regulation No. 16/KKI/PER/VIII/2006 concerning Procedures for Handling Cases of Alleged Violations of Discipline of Doctors and Dentists which has undergone several changes, including the Regulation of the Indonesian Medical Council Number 20 of 2014 concerning Procedures for Handling Cases of Alleged Violations of Discipline of Doctors and Dentists and Regulations Indonesian Medical Council Number 50 of 2017 concerning Procedures for Handling Discipline Complaints for Doctors and Dentists. The procedure for the complaint in question is to make a complaint, establish a Preliminary Examination Council, establish a Disciplinary Examination Council and finally prove.